PRODUKTIVITAS JAGUNG KOMPOSIT BERPENGAIRAN SPRINKLER SEBAGAI PANGAN DAN PAKAN DI LAHAN KERING IKLIM KERING NUSA TENGGARA BARAT - Ahmad Suriadi; Baiq Tri Ratna Erawati; Moh. Nazam (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
The Productivity of Composite Maize with Sprinkle Irigation for Food and Feed in Dry Land of West Nusa Tenggara. The potential of dry land in West Nusa Tenggara is about 1.8 million ha and about 30 % of them had been utilized. Maize is a plant that is quite adaptive to cultivate in dry land but that its productivity was low du to limited rainfall. Productivity of composite maize with sprinkler irrigation has been tested to obtain carrying capacity for feed and food in the village Jeringo Suela, East Lombok district during July-October 2011.The study was conducted in farmers' fields and was laid out with a randomized block design using 6 varieties of maize and was repeated three times (Srikandi Putih, Srikandi Kuning, Lagaligo, Lamuru, Anoman and Arjuna).Agronomic parameters were observed includes biomass, plant height, plant moisture content and yield (ton/ha).The data were analyzed using analysis of variance (ANOVA). Results showed that the variety effect plant height, cob height and yield, while the number of plants harvested, number of cob harvested and seed yield were not influenced by varieties. Lamuru variety has the highest yield by 8.266 t/ha, followed by Arjuna with 7.540 t/ha, while the lowest yield was found at Lagaligo with 6.117 t/ha. Carrying capacity of the biomass of maize to feed cattle in the location were exceeds the amount of cattle that are own by farmers (2 cattle/household). The highest carrying capacity was found at Lagaligo (without cobs) but low yield followed by Srikandi Kuning, Lamuru and Anoman varieties and the lowest was found at Srikandi Putih and Arjuna. Development of composite maize on dry season in dry land of semi-arid climate using sprinkler seem to be promoted technology that government may develop the irrigation sprinklers in other upland locations. Based on these results, it may suggest that the compositemaize may be planted on dry land and semi arid using sprinkler irrigation is Lamuru or Srikandi Kuning.Keywords: Composite maize, biomass, carrying capacity, fodder, dry land, sprinklerABSTRAKNusa Tenggara Barat memiliki lahan kering sekitar 1,8 juta ha, tetapi yang baru dimanfaatkan sebesar 30%. Jagung merupakan tanaman yang cukup adaptif dikembangkan di lahan kering namun produktivitasnya masih rendah karena curah hujan yang rendah. Tujuan penelitian untuk mengetahui produktivitas beberapa varietas jagung komposit berpengairan sprinkler sebagai pakan dan pangan yang ditanam pada musim kemarau. Penelitian dilakukan di lahan petani yang ditata dengan menggunakan Rancangan Acak Kelompok menggunakan enam varietas jagung (Srikandi Putih, Srikandi Kuning, Lagaligo, Lamuru, Anoman dan Arjuna) yang diulang tiga kali. Parameter agronomi yang diamati selanjutnya dianalisis menggunakan analisis keragaman (ANOVA) dan analisis ekonomi. Hasil pengkajian menunjukkan bahwa varietas berpengaruh nyata terhadap tinggi tanaman, tinggi letak tongkol dan hasil biji, sedangkan jumlah tanaman panen, jumlah tongkol panen dan rendemen biji tidak dipengaruhi secara nyata oleh varietas. Varietas lamuru memiliki hasil tertinggi yaitu 8,266 t/ha, kemudian diikuti oleh varietas Arjuna sebesar 7,540 t/ha, sedangkan terendah dihasilkan oleh varietas Lagaligo sebesar 6,117 t/ha. Daya dukung biomas jagung terhadap pakan ternak sapi Bali di lokasi pengkajian melebihi dari jumlah sapi yang dipelihara petani saat ini (2 ekor). Daya dukung biomasjagung yang tertinggi di peroleh pada varietas jagung Lagaligo (tanpa tongkol) namun hasilnya rendah dengan diikuti oleh varietas Srikandi Kuning, Lamuru dan Anoman dan yang paling rendah adalahvarietas Srikandi Putih dan Arjuna. Berdasarkan hasil penelitian ini, varietas yang anjurkan untuk ditanam pada lahan kering iklim kering berpengairan sprinkler adalah Lamuru atau Srikandi Kuning.Kata kunci: Jagung komposit, biomas, daya dukung, pakan ternak, lahan kering, sprinkler